The Modern Regime, Volume 1 - Taine, Hippolyte, 1828-1893; Rom, Svend; Durand, John, 1822-1908 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Modern Regime, Volume 1" by Hippolyte Taine is a historical account written during the late 19th century. This volume focuses primarily on Napoleon Bonaparte, examining his character, ideas, and the institutional changes he enacted that shaped modern France. Taine provides an analysis of Napoleon's personality as well as the socio-political climate of his time, offering insights into how his rule established a new state that deviates from the old regime. At the start of the work, Taine introduces the intricate relationship between Napoleon's character and his historical significance. He describes Napoleon as an individual shaped by unique circumstances, heritage, and ambitions, partly defined by his Corsican roots and Italian ancestry. The opening chapters also discuss how his early life experiences, political affiliations, and military genius contributed to his rapid rise to power. Taine examines Napoleon$1 (Bs formative years, his perspectives on France, and his interactions with key revolutionary figures, framing a narrative that emphasizes the complexity of the man who would eventually dominate European politics. (This is an automatically generated summary.)s
Part of the series Origins of contemporary France. [v.5-6]
Release date is 2008-06-22
Produced by Svend Rom and David Widger
Keywords: France -- Civilization; France -- Politics and government; France -- Social life and customs -- 19th century